Preventing the Adverse Effects of SARS-CoV-2 Infection and COVID-19 through Diet, Supplements and Lifestyle - Grant, William B.; Lordan, Ronan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book presents the latest research published in the Special Issue Preventing the Adverse Effects of SARS-CoV-2 Infection and COVID-19 through Diet, Supplements, and Lifestyle in the journal Nutrients. In this book, we explore the role of supplements, lifestyle choices, and nutritional status on COVID-19 patient outcomes and risk reduction.